2007
DOI: 10.4141/cjps07120
|View full text |Cite
|
Sign up to set email alerts
|

Impact and management of crested wheatgrass (Agropyron cristatum) in the northern Great Plains

Abstract: Vaness, B. M. and Wilson, S. D. 2007. Impact and management of crested wheatgrass (Agropyron cristatum) in the northern Great Plains. Can. J. Plant Sci. 87: 1023-1028. Crested wheatgrass [Agropyron cristatum (L.) Gaertn.] invades native prairie and reduces diversity in the northern Great Plains. Here we review the effects of crested wheatgrass on grassland communities and ecosystems, as well as potential strategies for controlling crested wheatgrass. Because of its tussock growth form and C 3 photosynthetic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Higher NDVI and CI were also observed on the north-facing slope in grasses. This between-slope difference increased over time in S. viridula and decreased with DOY in A. cristatum, an invasive species with earlier completion of annual growth cycles (Vaness and Wilson 2007). As observed at the leaf scale, canopy PRI was higher in shrubs of the north-facing slope in late summer.…”
Section: Seasonal Patterns Of Leaf Reflectancementioning
confidence: 64%
“…Higher NDVI and CI were also observed on the north-facing slope in grasses. This between-slope difference increased over time in S. viridula and decreased with DOY in A. cristatum, an invasive species with earlier completion of annual growth cycles (Vaness and Wilson 2007). As observed at the leaf scale, canopy PRI was higher in shrubs of the north-facing slope in late summer.…”
Section: Seasonal Patterns Of Leaf Reflectancementioning
confidence: 64%
“…Livestock grazing is the primary land use throughout the mixed-grass prairie. Although grazing can facilitate invasion in many ecosystems (Mack 1981;Sala et al 1986;Hobbs 2001;Brooks et al 2006), in mixed-grass prairie it has been found to have little effect on the richness of introduced species (Stohlgren et al 1999b), and to inhibit invasion by several palatable introduced perennial grasses (Murphy and Grant 2005; Stacy et al 2005;Vaness and Wilson 2007). This resistance to invasion in the presence of grazing may stem from the long evolutionary history of grazing in mixed-grass prairie (Milchunas et al 1988;Stohlgren et al 1999b;Lyman and Wolverton 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Invasive species are associated with a series of cascading effects on ecosystem function and integrity, lowering plant diversity (Pritekel et al 2006;Vaness and Wilson 2007). The invasion and expansion of Kentucky bluegrass in the Northern Great Plains has contributed to a decrease in native prairie biotic integrity and plant diversity (Cully et al 2003;DeKeyser et al 2009;Miles and Knops 2009a) and has altered plant community structure and function (DeKeyser et al 2013;Miles and Knops 2009a).…”
mentioning
confidence: 99%